1975
DOI: 10.1017/s0021859600072026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulphur fertilizers and of copper on the yield and composition of spring wheat grown in an sandy soil prone to surface compaction

Abstract: SUMMARYA condition known as ‘scorch” with symptoms similar to copper deficiency often occurs in dry weather on cereals grown on a sandy soil (at Woburn) with an unstable structure. Plants with symptoms contained more sulphur than normal and sulphur/ copper interactions were suspected.Sulphur fertilizers tested in two pot experiments with this soil did not induce copper deficienciesbut increased grain and straw yields of spring wheat especially at higher nitrogen rates. Yields were increased when the mature gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In 1972, copper had been deficient in leaves and stems of wheat plants showing 'scorch' symptoms (Bolton, 1975). Yields were not affected though copper content of the grain was increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In 1972, copper had been deficient in leaves and stems of wheat plants showing 'scorch' symptoms (Bolton, 1975). Yields were not affected though copper content of the grain was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Again, significant decreases occurred only in the aldicarb sub-plots treated in both years (P < 0.001). His analyses of 1973 crop samples showed that aldicarb residual activity increased nitrogen, sulphur and copper concentrations in grain by about l P h , although copper oxychloride increased % Cu in grain it did not affect yield (Bolton, 1975). Egg numbers were less in cumulatively treated aldicarb sub-plots than in 'residual' aldicarb but this was not so with formalin or dazomet.…”
Section: Grain Yields (Tlha At 85% Dm) Spring Wheat CV Kleiber Cmentioning
confidence: 99%
See 2 more Smart Citations
“…N/S ratios in the deficient herbage were as high as 40. Jones, Cowling & Lockyer (1972) have shown similar responses to sulphur by ryegrass using a wide range of soils from England and Wales and Bolton (1975) a response by spring wheat on a sandy loam soil from Woburn experimental station.…”
Section: Glasshouse Experimentsmentioning
confidence: 89%